Population trend of Periphylla periphylla in inner Trondheimsfjord - Solheim, Hilde (Institutt for biologi, 2012)
Periphylla periphylla (Scyphozoa, Coronatae) is a deep sea jellyfish first described by Péron & Lesueur in 1809. It is distributed in all of the world s oceans except for the Arctic. P. periphylla avoids light and is well adapted to a life in the dark. It performs diel vertical migrations (DVM) in the water column.Relatively recently, since first observation in Lurefjorden near Bergen in the 1970s, it has established dense populations in several Norwegian fjords including the Trondheimsfjord, the focus of this study. The main goal of this thesis was to estimate the current biomass of the P. periphylla population in the inner Trondheimsfjord (Beitstadfjorden), which has three smaller basins with different depths. Most of the data was collected by a Lightweight Video Profiling Platform (LVPP) which provided information on the vertical distribution of jellyfish, their numbers, and the size (CD: coronal diameter) of each individual. The population in Verrabotn, the shallowest and innermost basin of Beitstadfjorden, had a higher percentage of large individuals (CD >121 mm) than the other basins. Most of the jellyfish individuals in the other two basins tended to be small, with CD ≤ 40 mm. However, the total biomass estimated at each location was mainly made up by large P. periphylla. Comparing the present biomass estimate with a previous one in 2007, it appeared that the population had decreased.However, the presence of large numbers of small individuals of different sizes suggests that a successful local recruitment is still taking place.